2009
DOI: 10.1038/mp.2008.77
|View full text |Cite
|
Sign up to set email alerts
|

Bias in genetic association studies and impact factor

Abstract: and rs7000831; see Addington et al. 7 and http://www.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
47
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 6 publications
1
47
1
Order By: Relevance
“…The quantification of the likelihood of bias in genetic studies of MDD is a necessary subsequent step. A preliminary report suggests that a selective reporting bias may take place in these studies [60]. Third, hints of bias cannot exclude the possibility that some of the biomarkers included in this study may have good discriminatory power because they only suggest the presence of bias and are not proof thereof.…”
Section: Discussionmentioning
confidence: 99%
“…The quantification of the likelihood of bias in genetic studies of MDD is a necessary subsequent step. A preliminary report suggests that a selective reporting bias may take place in these studies [60]. Third, hints of bias cannot exclude the possibility that some of the biomarkers included in this study may have good discriminatory power because they only suggest the presence of bias and are not proof thereof.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the situation is surely much worse than what the discussion above would suggest because in addition to testing many hypotheses with a low likelihood of effects, investigators often exploit hidden flexibility in their data analysis strategies, allowing the true alpha level to rise well above the nominal alpha level (Simmons, Nelson, & Simonsohn, 2011; see also discussion by Ioannidis, 2005b, of "bias" andWagenmakers et al, 2012, this issue, on "fairy tale factors"). Moreover, the highest impact journals famously tend to favor highly surprising results; this makes it easy to see how the proportion of false positive findings could be even higher in such journals than it would be in less career-enhancing outlets (Ioannidis, 2005a;Munafò, Stothart, & Flint, 2009). Naturally, those areas within psychology that lend themselves to performing a great number of tests on a variety of variables in any given study, as well as areas in which underpowered studies are more common, are likely more prone to false findings than are other areas.…”
mentioning
confidence: 99%
“…The SNP8NRG243177 variant is of special relevance. Using a bioinformatic approach, Law et al 9 showed that this variant affects the binding of transcription factors to the 5 0 promoter region of the gene and is associated with the expression of a newly described isoform of the protein. Further studies are necessary to elucidate how this variant leads to pathological processes that increase the risk of psychosis, and how this genetic trait may interact with environmental factors.…”
mentioning
confidence: 99%